Radiofrequency-Induced Heating of Amalgam Restorations and Dental Implants During 1.5T Magnetic Resonance Imaging - Maryam Paknahad; Iman Khaleghi; Seyed Mohammad Javad Mortazavi (Tehran University of Medical Sciences, 2024)
Objectives: This study aimed to evaluate radiofrequency-induced heating of different amalgam restorations and dental implants during 1.5T magnetic resonance imaging (MRI). Materials and Methods: Standardized class I cavities (5 mm long, 3 mm wide, and 3 mm deep) were prepared on the occlusal surface of 45 extracted human third molars. The samples were restored by three different types of amalgam including Cinalux amalgam (non-gamma-2, spherical), GS-80 (non-gamma-2, admix), and GK-110 amalgam (non-gamma-2, admix in silver). As a separate intervention group (G4), five titanium mini drive-lock implants with 2mm diameter and 10mm length were also selected and mounted to the base of the Eppendorf tube with 3mm of the implants extending above the mounting putty. The box containing the specimens was placed parallel to the long axis of the standard head and neck coil of the MRI device (64MHz radio-frequency energy with 25kW amplifier, 1.5T). Temperature fluctuations of the metallic materials in each group were monitored during MRI scans using a calibrated thermometer. One-way ANOVA was used to compare temperature changes among the amalgam groups (P<0.05). Results: Temperature elevations ranged from 0.21°C to 0.70°C in amalgam restorations and from 0.35 to 0.47°C in dental implants. The temperature changes among the three amalgam agents were not statistically significant. Conclusion: According to our findings, the radiofrequency-induced heating of amalgam restorations and dental implants during MRI examination can be considered within acceptable ranges. Therefore, amalgam restorations and dental implants can be categorized as "MR safe" in terms of radiofrequency-induced heating during 1.5 T MRI.